Análisis artístico y estético de dos obras representativas de ghada amer, como referente para una propuesta plástica - Reátegui Lozano, María Isabel (2014)
This research workis aimed attheartistic and aestheticanalysis of the workof contemporaryartistGhadaAmer,takenas a reference forthe development of aplastic proposal. Based ona studyin the historical contextof conceptual art, to understand the differentapproaches and responsesin practiceare taking place,highlightingthe activityof artisticcreativity,aesthetic conceptsandartistic knowledge. Theidentity of the workcontinues to manifest itselfin the waythe vieweris responsible foritsthoughtfulconstruction andthis is the mostimportantexperienceof art.Suggestworksto arouseintellectual dispositionsaestheticstimuli,given thatinthe process of makinga work of artthere is alwaysa distance between theinitial conceptand the final product.